Comparative Effectiveness of Durian Peel and Coconut Shell Charcoal Biofilters for Calcium Carbonate Reduction in Groundwater: Experimental Study in Palu City - Hamidah; Nur Rismawati (Promotif : Jurnal Kesehatan Masyarakat, 2026)
Introduction: Water hardness caused by high concentrations of calcium carbonate is a persistent problem in many groundwater-dependent communities, including Palu City, Central Sulawesi, Indonesia. Excessive hardness reduces water acceptability, increases household maintenance costs, and contributes to scaling in pipes and storage systems. This study aimed to evaluate the effectiveness of two locally available organic-waste materials—durian peel charcoal and coconut shell charcoal—as low-cost biofilter media for reducing calcium carbonate concentrations in household well water. Method: A laboratory-based experimental design was applied using batch adsorption methods. Groundwater samples with an initial calcium carbonate concentration of 568 milligrams per litre were treated with varying masses of each adsorbent and different contact times. The study examined combinations of adsorbent mass and exposure time to determine optimal operating conditions. Calcium carbonate levels before and after treatment were measured using standard titration techniques to assess removal efficiency. Results: The results demonstrated that both organic-waste biofilters were capable of substantially lowering hardness levels. Durian peel charcoal achieved its best performance at a moderate adsorbent mass and short contact time, showing rapid adsorption kinetics and high affinity for hardness-related ions. Coconut shell charcoal also produced significant reductions but required greater mass and longer contact time to reach optimal effectiveness. The findings confirmed that adsorption performance was nonlinear and strongly influenced by operational parameters, material characteristics, and initial contaminant concentration. Comparison of the two media indicated that each possesses distinct advantages, highlighting the importance of context-specific optimisation for practical application. Conclusion: Overall, the study shows that transforming locally abundant agricultural wastes into biofilter media offers a feasible and affordable strategy for decentralised water treatment. The research contributes new comparative evidence on the use of durian peel and coconut shell charcoal for hardness reduction and supports their potential use in household-scale systems. If validated under field conditions, these findings may support the development of affordable household-scale strategies for improving the acceptability of drinking water in resource-limited communities.